Keseimbangan Akal dan Rasa dalam Kesehatan Jiwa: Tinjauan terhadap Pemikiran Ibnu Miskawaih dalam Tahdzīb al-Akhlāq - Khairunnisa, Khairunnisa; Burhanuddin, Nunu (Lembaga Yasin AlSys, 2024)
This research examines Ibn Miskawaih's thoughts in Tahdzīb al-Akhlāq related to the balance of reason and taste in mental health and its implications in modern life. Using the hermeneutic qualitative method, this research interprets Ibn Miskawaih's views on the relationship between morals, reason, and taste, and compares them with contemporary philosophical and psychological perspectives. According to Ibn Miskawaih, mental health is not only influenced by external factors, but also determined by the internal harmony between reason and taste. He emphasizes that self-control, wisdom, and good morals are key in regulating emotions and rationality in a balanced manner, which ultimately supports mental stability and happiness. The results show the relevance of Ibn Miskawaih's thought in the context of modern mental health. He taught that the balance between reason and taste is an important foundation for a healthy and meaningful life. By applying healthy moral principles, individuals can achieve better mental stability and happiness in their daily lives.